Process of integrating socio-technical bundles and measuring impacts using gender-responsive deed cycle framework - Gartaula, Hom Nath; Nchanji, Eileen; Puskur, Ranjitha; Ketema, Dessalegn Molla; Mukhopadhyay, Prama; Lutomia, Cosmas Kweyu; Thomas, George; Chadha, Deepali (2023)
Bundling social, technical, and technological innovations for women’s empowerment and climate resilience is a complex process (Johnstone et al. 2023). The process requires a systematic, participatory, iterative, and flexible approach with a co-designing mindset. This framework helps identify the entry points for co-designing socio-technical innovation bundles (STIBs), by incorporating the Reach-Benefit-Empower- Transform (RBET) framework within the classic DEED cycle framework.